Cloud Computing and Performance of County Governments In Kenya; a Case of the County Government of Nyandarua (Global Journal of Management and Business Research, 2020)
The general objective of the study was to investigate the effect of cloud computing on the performance of county governments in Kenya; a case of the county government of Nyandarua. The study#x2019;s specific objectives were to establish the influence of staff skills on performance of the County Government. The study was informed by Resource Based View Theory. The study adopted a correlational research design. The target population was 130 employees in ICT, communication, finance and administration department in the county government of Nyandarua. Simple random sampling was used to select a sample size of 97 respondents.
Keywords: cloud computing; performance; staff skills